Human Development Report 2004 - United Nations Development Programme (United Nations, 2004)
Cultural Liberty in Today’s Diverse World argues that states must actively devise multicultural policies to prevent discrimination on cultural grounds – religious, ethnic and linguistic. The Report states that the expansion of cultural freedoms, not suppression, is the only sustainable option to promote stability, democracy and human development within and across societies. Its overarching message is to highlight the vast potential of building a more peaceful, prosperous world by brining issues of culture to the mainstream of development thinking and practice. In delivering it’s message, the Report debunks the myths that have been used to deny expansions of cultural freedoms, showing that diversity is not a threat to state unity, not the source of inevitable clashes and not an obstacle to development.